2005
DOI: 10.5694/j.1326-5377.2005.tb07150.x
|View full text |Cite
|
Sign up to set email alerts
|

The Western Australian Audit of Surgical Mortality: advancing surgical accountability

Abstract: Objective: To describe the peer review process of the Western Australian Audit of Surgical Mortality (WAASM), selected outcomes and recommendations. Study design: Prospective audit using peer review of all cases of patients who died while under the care of a Western Australian surgeon between 1 January 2002 and 30 June 2004. Audit reviews were current to 30 September 2004. Participants and setting: 194 of 202 surgeons participated after a patient died under their care. Main outcome measures: Surgeon participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
45
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 19 publications
(34 reference statements)
2
45
0
Order By: Relevance
“…Little is known about the incidence and extent of comorbidities and complications in older Australians having surgery or the mortality associated with surgery 1 . A recent Western Australian study of patients who died after surgery found that most were old and had complex comorbidities 2 . Studies in North America and Europe have assessed postoperative outcomes for older patients in several surgical specialties 3 .…”
mentioning
confidence: 99%
“…Little is known about the incidence and extent of comorbidities and complications in older Australians having surgery or the mortality associated with surgery 1 . A recent Western Australian study of patients who died after surgery found that most were old and had complex comorbidities 2 . Studies in North America and Europe have assessed postoperative outcomes for older patients in several surgical specialties 3 .…”
mentioning
confidence: 99%
“…There is also evidence that they can be used poorly to ‘persecute’ individuals and ignore systems factors. However, there is good evidence that mortality reviews in particular engage clinicians in the process 12. Morbidity and mortality reviews can be seen as a structural indicator, in the sense that an organisation either undertakes this activity or not and undertakes it in a constructive manner or not.…”
Section: A Measurement Frameworkmentioning
confidence: 99%
“…There is considerable literature examining incident monitoring and adverse event tracking within the hospital environment1; in such areas as surgery,2 anaesthesia,3 intensive care4 and emergency departments 5. Unfortunately, literature pertaining to the prehospital environment has been limited6 7 until fairly recently 8 9.…”
Section: Introductionmentioning
confidence: 99%